Managing the Development of Regional Industrial Potential: Integrating Climate Finance into Investment Strategies - Irina P. Dovbiy; Zhanna A. Mingaleva; Evgeniy E. Zhulanov (Финансовый журнал)
The requirements for the implementation of climate policy are becoming increasingly important in the processes of formation of global and local value chains and directly affect the development of export potential of both individual economic entities and regions. The purpose of the study is to develop recommendations for improving the tools for managing the development of industrial potential of regional systems under the current conditions of financing the climate agenda in the amount of the country’s commitments. The article analyzes the investment and financial conditions and factors determining the region’s export potential in the context of the implementation of two strategies of the climate agenda — mitigation and adaptation to climate change. A comparative analysis was carried out for the regions located along the middle and lower reaches of the Volga River. The analysis included the following meso- and micro-level areas: investment climate characteristics; conditions for financing of economic entities; investment and innovation activity of the regions and commitment to ESG principles of business entities and regional authorities; quality and elaboration of regional investment standards and climate change adaptation plans, etc. The analysis has shown the impact of the climate agenda, implemented in climate change mitigation and adaptation strategies, on the export potential of the Russian regions under study. It is concluded that the regions are not sufficiently prepared for the growing challenges of the climate agenda and the financial system is poorly developed in relation to the climate agenda. It is shown that a clear identification and understanding of the factors and conditions contributing to the inclusion of national economic entities in value chains can help government agencies and economic entities make effective decisions on the implementation of measures to ensure the formation of favorable investment and financial conditions for managing the development of the region’s industrial potential.